MENAKAR HERMENEUTIKA DALAM KAJIAN SASTRA - IDA NURSIDA (Al Qalam, 2017)
The study of literature is signed by an inherent and important activity within it, i.e. interpretation. The activity of literature appreciation and literature criticism, both of its periphery and its orifice, deals with literature studies that should be interpreted. Every interpretation activity of literature works always involves in a hermeneutical process. Hence, hermeneutics occupies a crucial position and it is impossible to disregard it in the analyis of the literature works. Based on that explanation, hermeneutics is something important to discuss comprehensively in order to obtain sufficient understanding. Hermeneutics developed in the literature interpretation deals closely with the development of hermeneutical thoughts, especially on the history of philosophy and theology because it begins to appear from these two subjects. To understand hermeneutics in the literature interpretation, it is necessary to comprehensively understand the history and the concept of hermeneutics, especially dealing with three variants of hermeneutics which develop in the tradition of modern hermeneutics: methodological or theoritical hermeneutics, philosophical hermeneutics, and critical hermeneutics. by understanding these three variants, it enables us to have sufficient understanding on hermeneutics in the literature studies.